Effects of plasma treatment on water sorption in viscose fibres - Devetak, Miha (Materiali in tehnologije, 2012)
We investigated water sorption in viscose nonwoven fibres manufactured by Tosama d.d. with the surface density of 175 g/m2. A comparison between untreated fibres and by oxygen plasma treated fibres was made using optical polarization microscopy. Plasma treatment was done for 10 minutes at pressure of 75 Pa at current of 250 mA at the power of 500 W. Swelling was characterized by measurements of fibre diameter. Modifications of intensity of the polarized light transmitted through the fibre were measured as a function of time of exposure to water. Characteristic swelling and intensity modification times were resolved for untreated and oxygen plasma treated fibres. The swelling time of oxygen plasma in comparison to untreated plasma is reduced by the factor of 0.54 and intensity change time by the factor of 0.4. From the characteristic swelling and intensity change times it was concluded that oxygen plasma treatment of viscose increases the speed of water sorption.
Keywords: plasma treatment; plazemska obdelava; viscose; viskoza; nabrekanje; optical polarization microscopy; optična polarizacijska mikroskopija